Development of new bilberry (Vaccinium myrtillus L.) based snacks: Nutritional, chemical and bioactive features - Pires, Tânia C.S. (2018)
The sustainable exploitation of fruit and cereal processing is being conducted to produce novel food products with promising nutritional properties and high content in added value compounds. Herein, three bilberry fruit-based snacks supplemented with edible petals and fruits were characterized for their nutritional properties and chemical composition. The phenolic profile, antioxidant, antibacterial and hepatotoxic properties were analyzed. Protein (3–4 g/100 g dw) and carbohydrates (94.3–94.8 g/100 g dw) represented the major macronutrients. The combination of bilberry fruits with edible petals, calendula and rose, improved the nutritional and phytochemical input in organic acids and tocopherols content, respectively. Also, the supplementation with apple and goji fruits provided higher content in phenolic acids and anthocyanins (up to a 9-fold higher concentration, 199.7 µg/g of extract), also resulting in a higher antioxidant and antibacterial activities. The results obtained can contribute for the development of novel sustainable and healthier snacks for the food industry.